Depression Screening and Measurement-Based Care in Primary Care. (November 2020) - Siniscalchi, Kimberly A.; Broome, Marion E.; Fish, Jason; Ventimiglia, Joseph; Thompson, Julie; Roy, Pratibha; Pipes, Ronny; Trivedi, Madhukar
The health issue addressed is the unmet need to universally screen and treat depression, which is one of the most common mental health disorders among adults in the United States. The US Preventive Services Task Force recommends screening adults for depression in primary care and using evidence-based protocols. This quality improvement project implemented VitalSign6, a measurement-based care program, to improve depression screening and treatment of adults in primary care at an academic medical center. A pre-post design was used to determine effectiveness of changes in screening, outcomes, and satisfaction. Of 1200 unique adult patients, 95.4% received initial screening. Providers diagnosed and administered measurement-based care to 236 patients. After 14 weeks, 27.5% returned for at least 1 follow-up. Results showed a statistically significant decrease in self-reported depression scores from baseline to follow-up. VitalSign6 was effective in improving identification and management of depression in primary care.